2015
DOI: 10.1111/1750-3841.12849
|View full text |Cite
|
Sign up to set email alerts
|

Total and Inorganic Arsenic in Iranian Rice

Abstract: It is well known that arsenic (As) exposure, particularly to inorganic species (i-As), has adverse effects on humans. Nowadays, the European Union (EU) has still not regulated the maximum residue limit of As in commercial samples of rice and rice-based products, although it is actively working on the topic. The European Food Safety Authority (EFSA) is collecting data on total arsenic (t-As) and i-As from different rice-producing regions not only from EU countries but also from other parts of the world to final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
3
9
1
3
Order By: Relevance
“…A great amount of arsenic is removed during the rice polishing [ 21 , 50 52 ]. Besides, variation in the arsenic concentration may occur due to different cultivars, geography, environment, water quality, and growth conditions [ 21 , 24 , 25 , 29 , 30 , 37 , 51 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…A great amount of arsenic is removed during the rice polishing [ 21 , 50 52 ]. Besides, variation in the arsenic concentration may occur due to different cultivars, geography, environment, water quality, and growth conditions [ 21 , 24 , 25 , 29 , 30 , 37 , 51 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cano-Lamadrid i wsp. prowadzili badania dotyczące zawartości arsenu nieorganicznego (i-As) i całkowitej zawartości arsenu (t-As) w irańskim ryżu [12]. Analizie poddano 15 próbek ryżu zebranych z najważniejszych rejonów kraju zajmujących się produkcją ryżu.…”
Section: Wyniki Przegląduunclassified
“…Średnia zawartość i-As wynosiła 82 µg/kg, a t-As -120 µg/kg. Według autorów taka zawartość arsenu w ryżu nie stwarza niebezpieczeństwa dla zdrowia człowieka, ponieważ jest niższa od norm chińskich (limit i-As w ryżu wynosi 150 µg/kg) i norm wyznaczonych przez Organizację Narodów Zjednoczonych do spraw Wyżywie-nia i Rolnictwa (Food and Agriculture Organization of the United Nations -FAO), wynoszących dla ryżu do 200 µg/kg i-As [12].…”
Section: Wyniki Przegląduunclassified
“…139 Another study extracts iAs with TFA and determination is by HPLC-HG-AFS. 172 White rice (SRM 1568b white rice) was recently released by NIST and it is certified for arsenic speciation (DMA, MA, and iAs). To date, two studies analyze it to evaluate the accuracy of their methods; one is based on As species in rice by CE-ICP-MS, 218 and the other is focused on rice-based products for infants and young children using HPLC-ICP-MS. 248 Finally, only one study was found that analyzes NMIJ 7405a hijiki, and the reported iAs value is in agreement with the certified one.…”
Section: -247mentioning
confidence: 99%